Structural Characterization of Polysaccharides in Waste Liquor Produced by Wet Decortication of Sesame Seeds - Li, Yao-Ran; Xu, Shuai; Zhang, Run-Yang; Yang, Ming-Xuan; Liu, Hua-Min; Wang, Xue-De (Frontiers in Nutrition, 2022)
The wet decortication of sesame seeds produces wastewater containing diverse minerals and organic pollutants that could be valuable resources for the food industry. This investigation aimed to reclaim, purify, and characterize the polysaccharides contained in the waste liquor from the sesame decortication industry. The purified polysaccharide fractions were characterized using monosaccharide analysis, GPC (high-performance gel permeation chromatography), FT-IR (Fourier-transform infrared) spectroscopy, methylation analysis, 1D and 2D NMR analysis, and thermal analysis. Four fractions were found (SSP-1,-2,-3, -4), of which SSP-2 was proportionately the largest and most interesting. The backbone of SSP-2 is mainly composed of (1→2,4)-β-D-Xylp residues with side chains connected to the O-4 position, with many T-β-D-Galp and (1→5)-α-L-Araf residues, and fewer (1→4)-α-D-Glcp, (1→2)-α-L-Rhap, T-α-L-Araf, and (1→2)-β-D-GlcpA residues. An efficient method for removing the polysaccharides would simplify wastewater treatment while finding a use for them would benefit the sesame, food, and pharmaceutical industries.